2021
DOI: 10.3390/cancers13164067
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Relaxometry for Tumor Cell Density Imaging for Glioma: An Exploratory Study via 11C-Methionine PET and Its Validation via Stereotactic Tissue Sampling

Abstract: One of the most crucial yet challenging issues for glioma patient care is visualizing non-contrast-enhancing tumor regions. In this study, to test the hypothesis that quantitative magnetic resonance relaxometry reflects glioma tumor load within tissue and that it can be an imaging surrogate for visualizing non-contrast-enhancing tumors, we investigated the correlation between T1- and T2-weighted relaxation times, apparent diffusion coefficient (ADC) on magnetic resonance imaging, and 11C-methionine (MET) on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Along with others, we have reported that the T1- and T2-relaxation properties of tumor tissue tightly correlate with the IDH mutation status of LrGGs 16 , 27 . These observations were obtained either by employing conventional MR relaxometry techniques 16 , 28 or by newly developed magnetic resonance fingerprinting technology 29 . However, neither technology has been incorporated into routine LrGG imaging studies as yet due to additional requirements in terms of scan time 16 or sequence and postprocessing optimization 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with others, we have reported that the T1- and T2-relaxation properties of tumor tissue tightly correlate with the IDH mutation status of LrGGs 16 , 27 . These observations were obtained either by employing conventional MR relaxometry techniques 16 , 28 or by newly developed magnetic resonance fingerprinting technology 29 . However, neither technology has been incorporated into routine LrGG imaging studies as yet due to additional requirements in terms of scan time 16 or sequence and postprocessing optimization 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid tracer-based positron emission tomography (PET) is one of the imaging modalities that has thoroughly been investigated for NET visualization. Notably, several stereotactic tissue sampling studies demonstrated that Met-PET well correlates with glioma cell density [ 5 , 11 , 12 , 18 ] and that its diagnostic accuracy was higher than that of conventional MRI [ 20 ]. However, incorporating amino acid tracer-based PET into daily clinical practice has still not been achieved and is still considered an investigational imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this research trend, our group investigated the possibility of using MR relaxometry to delineate NET. Our previous finding suggested that MR relaxometry, especially T1-relaxation time, helped to identify NET [ 12 ]. As MR relaxometry requires an additional 20 min scan and is still not a routine clinical imaging technique, this research study tested the hypothesis that the ratio of T1- and T2-weighted images (T1w/T2w-ratio map: rT1/T2) could be an imaging surrogate of MR relaxometry and could further be used for visualizing NET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations